Marketing Communication Strategy to Reopen A Business Venture - Mohammad Fahreza (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2019)
The research aims to find the best marketing communication strategy for reopening the new business venture that engages in washing services in specialized products such as bags and shoes. This research used a descriptive approach. The research was conducted through FGD and market surveys. The observed variable was the perception of cleaning service in terms of the interests, activities, behavior, needs and desires of consumers. The result of the research shows that the approach of restarting the business is looking at a business venture as a startup. The business branding of the new venture is in a disadvantaged position compared to its competitors because it has just opened; therefore marketing strategy is to build and enhance business branding by communicating information about business services to potential customers through social media, key persons, and word of mouth. It is expected to be able to communicate the service features and a variety of information about service, price and discount, location, and other profiles of new ventures. The marketing communication strategy is based on the stages of a customer's journey to decide on a purchase, ranging from awareness, education, consideration, purchase, loyalty, to advocacy.   JEL Classification:  L21, L84, M30